Analysis of the Correlation Between Learning Motivation and Critical Thinking Skills of Students on the Subject of Particle Dynamics - Anindyta Nur Rizkyana Safitri; I Gede Nengah Prasi (Universal Education Jurnal Teaching and Learning, 2024)
This research uses descriptive qualitative-quantitative research which aims to describe critical thinking skills on particle dynamics material. The population used was physics students at Malang State University and this sample was chosen randomly using a random sampling technique. This study uses an instrument and a questionnaire. The instrument used was as many as 5 elaboration questions about particle dynamics based on critical thinking indicators according to Ennis and the learning motivation questionnaire. From the research that has been done, it is obtained that the critical thinking skills of Malang State University students are sufficient with a total percentage value of 68.30%. The highest percentage average score of each indicator is the second indicator that determines the basis for decision making by 87.7%, then the fourth indicator is 76.4%, the third indicator is 70.7%, the first indicator is 58.5% and the lowest percentage is the average score the average of each indicator is the fifth indicator with a percentage of 48.1%. So, it can be concluded that the first and fifth indicators are still relatively low. Students' motivation in learning at the State University of Malang is quite sufficient at 72.71%. The percentage of each aspect on average reaches almost 50%.